Assessment of Poplar Germplasm for Resistance Against Alternaria alternata Causing Leaf Spot of Poplars in Himachal Pradesh - Sharma, R. C.; Sharma, Sanjeev; Khurana, D. K. (Indian Forester, 1999)
Growing demand of Poplar wood for manufacture of fruit boxes, plyboard, match sticks due to its fast growth and colourless wood have led to extensive plantation of this species. This has resulted in severe outbreak of a number of diseases. Alternaria alternata is one of the most destructive pathogens of Populus species in nurseries resulting in premature defoliation. During 1997, an expcriment was conducted to assess 232 different cloneslhybrids of P. ciliata and P. deltoides against A. alternata. Out of 29 clones and 75 hybrids of P. ciliata, 3 clones and 22 hybrids remained free from the disease. In 11 clones and 2 hybrids of P. ciliata, disease reaction varied from resistant to moderately resistant. Out of 73 clones and 7 hybrids of P. deltoides, 64 clones and 7 hybrids remained free from the disease. All the 46 families of P. deltoides screened were found free from the disease.